Design of Tunnel Magnetoresistive-Based Circular MFL Sensor Array for the Detection of Flaws in Steel Wire Rope. (15th September 2016) - Xiucheng, Liu; Yujue, Wang; Bin, Wu; Zhen, Gao; Cunfu, He
Abstract : Tunnel magnetoresistive (TMR) devices have superior performances in weak magnetic field detection. In this study, TMR devices were first employed to form a circular magnetic flux leakage (MFL) sensor for slight wire rope flaw detection. Two versions of this tailor-made circular TMR-based sensor array were presented for the inspection of wire ropes with the diameters of 14 mm and 40 mm, respectively. Helmholtz-like coils or a ferrite magnet-based magnetizer was selected to provide the proper magnetic field, in order to meet the technical requirements of the TMR devices. The coefficient of variance in the flaw detection performance of the sensor array elements was experimentally estimated at 4.05%. Both versions of the MFL sensor array were able to detect multiple single-broken wire flaws in the wire ropes. The accurate axial and circumferential positions of these broken wire flaws were estimated from the MFL scanning image results. In addition, the proposed TMR-based sensor array was applied to detect the MFL signal induced by slight surface wear defects. A mutual correlation analysis method was used to distinguish the signals caused by the lift-off fluctuation from the MFL scanning image results. The MFL sensor arrays presented in this study provide inspiration for the designing of tailor-made TMR-based circular sensor arrays for cylindrical ferromagnetic structural inspections.